PERAN LAGU GARUDA PANCASILA TERHADAP RASA CINTA TANAH AIR INDONESIA PADA SISWA KELAS V DI SD NEGERI 20 MAMBOK SINTANG - Rusdi Rusdi; Dwi Cahyadi Wibowo (STKIP Persada Khatulistiwa Sintang, 2023)
This study aims to describe the role of the Garuda Pancasila song in fostering a sense of love for the Indonesian homeland and the impact of the Garuda Pancasila song on the love for the Indonesian homeland for fifth grade students at SD Negeri 20 Mambok, Sintang. The research was conducted using a qualitative reasearch design with a taxonomic analysis approach. With subjects selected and decided purposively, i.e. educators, school managers, and students as well as experts in music education and learning. Data collection techniques are carried out by utilizing perceptions or observations, music practice, and interviews. In this study it was found that, a sense of love for the Indonesian homeland had been instilled from an early age in SD Negeri 20 Mambok Sintang, before learning began the principal gave rules so that all students and teachers in the school listened to several national songs, one of the songs that was often used was Garuda Pancasila song. Apart from that, the role of the Garuda Pancasila song has an indirect impact on the feeling of love for the homeland and defending the country, this can be seen when the song is played and listened to, the attitude of the students and teachers is ready and serious in listening. and fifth grade students can sing songs well and memorize song lyrics very well in these fifth grade children.